Bridge Network Decisions with Mobile Technology Integration - Ozer, Ekin; Tran, Thanh; Ramadan, Wasim; Malekloo, Arman; ICASP14; Di, Xuan (My University, 2023)
The interconnectedness between structural failure probabilities and systemic features is crucial in civil infrastructure safety and integrity assessment in post-disaster applications. The combination of systemic reliability with transportation and health services demand can aid in optimizing the response strategies of the bridge population and planning effective disaster?related decisions. This paper aims to improve upon the conventional bridge health monitoring solutions by upscaling the monitoring paradigm into urban regions and transportation networks and applying mobile and smart sensing techniques together with an innovative reconnaissance procedure.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED